John Dewey, Robert Pirsig, and the Art of Living - Granger, D. author. aut Link
XII, 307 p.
Keywords: This book explores the writings of philosopher and educator, John Dewey, in order to develop an expansive vision of aesthetic education and everyday poetics of living. Robert Pirsig's best-selling book, Zen and the Art of Motorcycle Maintenance , provides concrete exemplifications of this compelling yet unconventional vision.